PLANT DIVERSITY - Kunming Institute of Botany (Kunming Institute of Botany. Chinese Academy of Sciences, 2016)
Plant Diversity (formerly Plant Diversity and Resources) is an international plant science journal that publishes substantial original research and review papers that advance our understanding of the past and current distribution of plants, contribute to the development of more phylogenetically accurate taxonomic classifications, present new findings on or insights into evolutionary processes and mechanisms that are of interest to the community of plant systematic and evolutionary biologists. While the focus of the journal is on biodiversity, ecology and evolution of East Asian flora, it is not limited to these topics. Applied evolutionary issues, such as climate change and conservation biology, are welcome, especially if they address conceptual problems. Theoretical papers are equally welcome. Preference is given to concise, clearly written papers focusing on precisely framed questions or hypotheses. Papers that are purely descriptive have a low chance of acceptance.
Keywords: Botany : Periodicals; Plants : Periodicals